Exchange Rate and Stock Prices in Nigeria: Firm-level Evidence (2020)
This study examined the symmetry and asymmetry of the exchange rate-stock price nexus for 54 firms listed on the Nigerian Stock Exchange (NSE). We employed asymmetric Auto Regressive Distributed Lag (ARDL) model proposed for time series, using daily data for the period from December 12, 2001 to December 8, 2017. For comparative purposes, we also estimated the symmetric version. In the linear model, we found insignificant relationship between exchange rate and stock prices in most of the firms. Similarly, in the NARDL estimations, we observed that exchange rate movements do not have asymmetric impacts on stock prices in almost all the firms. In line with these findings, we recommend that financiers cannot make informed investment decisions using information obtained from the exchange rate market. In addition, the monetary authorities may need to reconsider the strict use of exchange rate as a policy tool to attract foreign portfolio investment